Modifying Effect of Tungsten on Vacuum Condensates of Iron - Barmin, A. E.; Sobol’, O. V.; Zubkov, A. I.; Mal’tseva, L. A. (Pleiades Publishing, Ltd., 2015)
Laws of the structure formation, as well as the strength properties and thermal stability of vacuum condensates of the Fe–W system have been studied. It has been found that the alloying of iron foils with tungsten to 1 at % makes it possible to disperse the grained structure of the condensates to nanometric dimensionality and to markedly enhance their strength properties and recrystallization temperature. Thus, the foils containing ~0.8% tungsten and grains of about 50 nm in size exhibit the hardness 5.5 GPa and recrystallization temperature 800°C. These results can be used to devise compositions of the steels designed for subsequently obtaining high-strength and thermostable nanostructural states.
Keywords: vacuum condensates; modification; segregation; nanocrystallized materials